Multicenter study of carbon‐ion radiation therapy for nonsquamous cell carcinomas of the oral cavity - Hiroaki Ikawa; Masashi Koto; Yusuke Demizu; Jun‐ichi Saitoh; Hiroaki Suefuji; Tomoaki Okimoto; Tatsuya Ohno; Yoshiyuki Shioyama; Ryo Takagi; Kazuhiko Hayashi; Kenji Nemoto; Takashi Nakano; et al. (Cancer Medicine, 2019)
Abstract Background The aim of this study was to evaluate the efficacy and safety of carbon‐ion radiation therapy for nonsquamous cell carcinomas of the oral cavity in a multicenter study. Methods Retrospective analysis of the clinicopathological features and outcomes of 76 patients with oral nonsquamous cell carcinomas with N0‐1 M0 status and were treated with carbon‐ion radiation therapy at four institutions in Japan between November 2003 and December 2014 was performed. Results Salivary gland carcinoma, mucosal melanoma, and three other carcinomas were found in 46, 27, and 3 patients, respectively. T1‐3, T4a, and T4b disease was diagnosed in 27, 18, and 31 patients, respectively. Median follow‐up period was 31.1 months (range, 3‐118 months). Three‐year local control, progression‐free survival, and overall survival of all patients were 86.8%, 63.1%, and 78.4%, respectively. Multivariate analysis showed T classification (T4) to be a significant independent poor prognostic factor for local control. Acute grade 3 mucositis was observed in 38 patients. Grades 3 and 4 late morbidities were observed in 9 and 4 patients, respectively. No grade 5 late toxicity was observed. Conclusions Oral nonsquamous cell carcinomas could be treated effectively, with acceptable toxicity, by carbon‐ion radiation therapy.